Influencia de la formación investigativa en el plan de trabajo de investigación en estudiantes del quinto nivel Facultad de Ciencias de la Educación y Humanidades UNAP Iquitos 2023 - Vargas Flores, Blanca Azucena (2025)
The primary objective of this study was to explain the influence of research training on the development of research work plans among fifth-level students at the Faculty of Education and Humanities, UNAP, Iquitos, in 2023. To achieve this, explanatory type research was employed, utilizing a bivariate, cross-sectional, and field research design. The sample consisted of 71 university students, who were assessed using a written performance test and an observation guide, both of which were previously validated by experts. The study confirms that research training significantly influences the development of research work plans among fifth-level students at FCEH-UNAP. The multiple regression model demonstrates high statistical significance (p < 0.01) and explains 69.7% of the variability in the research plan, considering the dimensions of curriculum development, teaching-learning strategies, and research skills. Additionally, the model’s assumptions were verified, including independence of residuals (Durbin-Watson = 1.765), homoscedasticity (Levene p = 0.134), normality of residuals (p = 0.200), and absence of collinearity. These findings support the validity of the model and reinforce the hypothesis that robust research training is a key determinant in the planning and execution of research in higher education.